(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Multiple sclerosis (MS) is an autoimmune disease which is inflammatory in nature and shows gliosis and demyelination which lead to acute and chronic symptoms impairing the quality of life due to disability. Presence of immune-mediated response in Central Nervous System leads to the above presentation. MS is the most common condition of CNS which causes disability. Treatment of Multiple Sclerosis consists of treating the exacerbations along with slowing the disease process and including symptomatic therapies. The most invalidating symptom in people with MS is Fatigue. This case reports shows the effectiveness of endurance and respiratory training towards the delaying the progression of symptoms in MS.